Improving Speaking Skills Through Peer Teaching Based on Behavioral Light Skinner - Ely Fadilah; Miftahul Huda; Ma’rifatul Munijah (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
Improving speaking skills in Arabic language learning is not only limited to the use of conventional methods, but can be more optimal by applying the Peer Teaching method based on B.F. Skinner's Behavioral theory. The purpose of this study is to interpret the improvement of speaking skills through the Peer Teaching method based on Behavioral Light Skinner. The object of this study was the students of the Darul Lughoh boarding school at the Darussalam Islamic Boarding School, Blokagung. This study uses a qualitative method with a case study approach. The source of informants in this study were students of the Darul Lughoh boarding school, Darussalam Islamic Boarding School, Blokagung. Data collection techniques in this study were carried out through observation, interviews, and documentation studies. The data analysis technique in this study used the interactive technique of the Miles and Huberman model, which consists of three main stages, namely data reduction, data presentation, and drawing conclusions. The results of this study concluded that improving speaking skills through the Peer teaching method based on Behavioral Light Skinner, namely accelerating vocabulary and sentence structure mastery, increasing retention and understanding of speaking concepts, positive feedback models increasing self-confidence.